Management of pests of cowpea using red ant, oecophylla smaragdina (fab.) - Amida Saparya (Department of agricultural entomology, College of agriculture, 2015)
The experiment entitled “Management of pests of cowpea using red ant, Oecophylla smaragdina (Fab.)” was undertaken at the College of Agriculture, Padannakkad during the period from March 2014 to June 2015. The seasonal variation in population of red ant was measured by counting the number of live nests over one year and the ant activity was measured during 3 seasons for a period of 30 days in each. The interaction was measured by colonizing red ant on plants dominated by other ants. The effect of food provisioning was studied by counting the live nests constructed on host plants provided with and without artificial food. The experiment on the eradication of competitive ants was done on cashew and cowpea. Pest management efficacy and impact of commonly used pesticides on red ant were also studied. In the study on seasonal variation in red ant population, it was observed that there was a general tendency of decrease in the number of nests during monsoon period. The mean ant activity, temperature and relative humidity in each season show that relation between ant activity and temperature was positively correlated. The ant activity was found less during morning hours when temperature was less. The interaction between O. smaragdina and Tetraponera nigra and Paratrchina longicornis was found submissive and they coexist. The yellow crazy ant Anoplolepis gracileps was found dominant over O. smaragdina and severely affected red ant colony establishment. On an average, the number of nests on cashew trees provisioned with food increased 10 times where as it was only 1.35 times when food was not provided over a period of 33 days. In the competitive ant eradication experiment, Azadirachtin 0.1 % sprayed on the entire crop was observed as best on cashew and DDVP 76 EC @ 0.076 % sprayed on entire crop in cowpea. In the pest management efficacy study, maximum number of pods and leaves were attacked by aphids in control and red ant harboured plants and POP treated plants were on par. The result on yield parameters shows that there is no significant difference between the treatments in the case of pod number and pod length. Fresh weights of the pods were significantly low in control but POP treated and red ant colonized plants were on par. In the study on the impact of pesticides on red ant, DDVP 0.076 % treatment most adversely affected the red ant nest building and activity followed by Azadirachtin 0.03 % and Bordeaux mixture 1 % and least by Tobacco decoction 2.5 %